Dynamic-mismatch mapping for digitally-assisted DACs - Tang, Yongjian (Analog Circuits and Signal Processing, 2013)
This book describes a novel digital calibration technique called dynamic-mismatch mapping (DMM) to improve the performance of digital to analog converters (DACs).  Compared to other techniques, the DMM technique has the advantage of calibrating all mismatch errors without any noise penalty, which is particularly useful in order to meet the demand for high performance DACs in rapidly developing applications, such as multimedia and communication systems.   ·         Discusses fundamental performance limitations of digital to analog converters and summarizes existing design/calibration techniques; ·         Introduces a novel digital calibration technique, called dynamic-mismatch mapping (DMM) to improve both static and dynamic performance of DACs; ·         Includes two state-of-the-art DAC design examples with in-depth discussion.